2002
DOI: 10.1046/j.1440-1630.2002.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Australian occupational therapists working in adult physical dysfunction settings: What treatment media do they use?

Abstract: The use of exercise‐based treatment media, which target the underlying basis of physical dysfunction but can overlook the psychological, social, and cognitive aspects of human function, has been criticised as being incongruent with occupational therapy philosophy. This study aimed to explore the treatment choices of Australian occupational therapists in adult physical dysfunction settings, to identify the influences on those choices, and to determine whether the use of client priority assessments impacts on tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…In accordance with other studies (e.g. McEneany et al, 2002;Rodger et al, 2005), this indicates that facilitation of learning is a core clinical competency. Participants agreed that the 4QM provides a useful framework through which to understand and implement teaching-learning within the context of occupational therapy.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with other studies (e.g. McEneany et al, 2002;Rodger et al, 2005), this indicates that facilitation of learning is a core clinical competency. Participants agreed that the 4QM provides a useful framework through which to understand and implement teaching-learning within the context of occupational therapy.…”
Section: Resultssupporting
confidence: 92%
“…Both groups highlighted concerns over the utility of the model with particular populations, particularly those with cognitive impairments, despite evidence that occupational therapists regularly engage teaching-learning in working with such clients (McEneany et al, 2002). Interestingly, Vygotsky (1978) acknowledged the need for scaffolding to support insufficiency in cognitive processes at various stages of learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey of the treatment media that Australian occupational therapists who work in adult physical dysfunction settings use, education and counselling was ranked as the most frequently used treatment, with three quarters of the respondents stating that they use it often or most of the time. 28 Participants from the same hospital provided varying answers to the question about which team member/s provides the most written information to patients and carers, indicating a lack of knowledge about their team members' practices. The low proportion of health professionals in this study who reported providing written information to patients and carers may be due to their assumption that other team members have or will do so.…”
Section: Discussionmentioning
confidence: 99%
“…Development of the questionnaire was partially guided by previous surveys of practice patterns of occupational therapists with different patient populations (Koh, Hoffmann, Bennett & McKenna, 2009;McEneany, McKenna & Summerville, 2002;Rodger, Brown & Brown, 2005). Questions in section 1 used mainly fixed response category options asking about practice setting, caseload and length of time they had previously worked in dementia care.…”
Section: Measurementioning
confidence: 99%